Desain dan Implementasi Pembelajaran PAI Berbasis Eksperiental Learning dalam Membentuk Soft Skill Komunikasi Siswa Kelas XII di MA Sumbersari Kowang - Muhammad Abdul Mubin; Tomy Afandi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the effectiveness of the Field Practice Experience (PPL) Program implemented for grade XII students of MA Sumbersari Kowang, particularly in the context of developing and improving communication soft skills. This descriptive qualitative research uses a case study approach by analyzing data from participant observation, interviews, and document analysis. The results of the study indicate a significant and measurable increase in students' communication soft skills after the PPL. The PPL program provides a concrete experience that forces students to face real communication challenges. This experience is then followed by the creation of activity reports. This phenomenon confirms that PPL is a pedagogical intervention that successfully internalizes communication soft skills, in accordance with the principles of Experiential Learning. PPL at MA Sumbersari Kowang has proven to be very effective in developing the communication soft skills of grade XII students. Through direct experience in the field, it has a significant impact on students' discipline and responsibility, in addition to communication soft skills. Students' abilities are evident through the skills of asking questions, giving and receiving constructive and supportive feedback during discussions in learning. It is recommended that schools integrate soft skills assessment explicitly and structure it in the PPL curriculum in the future. Keywords: Communication Soft Skills, Experiential Learning, Islamic Education learning